2013
DOI: 10.1007/s00167-013-2638-1
|View full text |Cite
|
Sign up to set email alerts
|

The radiological outcomes of patient-specific instrumentation versus conventional total knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 24 publications
2
84
1
Order By: Relevance
“…Although Noble et al [24] noted a decrease in operative times with the use of CCGs by 7 minutes, Hamilton et al [17] found the use of traditional instrumentation to be shorter than CCGs by 4 minutes. In addition, the results of several Level II and Level II studies have also been mixed to this regard [6,8,11,25]. No difference in either tourniquet time or total operative time was seen in our study.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Although Noble et al [24] noted a decrease in operative times with the use of CCGs by 7 minutes, Hamilton et al [17] found the use of traditional instrumentation to be shorter than CCGs by 4 minutes. In addition, the results of several Level II and Level II studies have also been mixed to this regard [6,8,11,25]. No difference in either tourniquet time or total operative time was seen in our study.…”
Section: Discussionmentioning
confidence: 46%
“…Most reports have focused on the avoidance of alignment outliers and the potential cost-effectiveness of this technology, demonstrating mixed results [6, 14, 23-25, 33-35, 39]. With regard to component and overall alignment, studies have failed to consistently demonstrate an improved accuracy with the use of CCGs versus standard instrumentation [6,11,18,24,40]. Furthermore, the costeffectiveness of this technology has not been proven, because the potentially decreased operative times and instrument trays required might not offset the additional costs of preoperative imaging and CCG fabrication [6,33,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of five Level II studies demonstrated no benefit with PSI [2,3,25] and one study demonstrated improved tibial component rotation [30]. The final Level II study demonstrated a greater number of alignment outliers when PSI was used [8].…”
Section: Domentioning
confidence: 93%
“…Among the studies providing a lower level of evidence, the results were again split. A Level II study [3] and two Level III studies [5,21] demonstrated faster operative times with PSI, whereas another Level II [8] and a Level III study failed to demonstrate quicker surgery with PSI [1].…”
Section: Domentioning
confidence: 99%